Segurança jurídica e vinculação das decisões judiciais: análise da relação entre a formação da coisa julgada e a súmula vinculante no direito brasileiro - Côrtes, Osmar Mendes Paixão (2007)
This dissertation analyses the relationship between res judicata and precedent in the Brazilian Law, examining the juridical safety and the binding of the judicial decisions. Initially, considerations are made about juridical safety, exploring themes such as its historical relevance, effectiveness and the development of juridical safety in Brazilian Law. Next comes the study of the res judicata, essential to the effectiveness of the juridical safety, detailing how it is regulated in different juridical contexts British, American, Portuguese and Brazilian and emphasizing the current tendency towards its relativization. The study also examines the binding of the judicial decisions in the common law and the civil law in order to understand the instrument of precedent (stare decisis), and analyzes the Brazilian experience with binding decisions. Recent changes in the legislation have included the precedent in the Brazilian order, and its nature, functions and procedures are examined in this dissertation. The central debate revolves around the relationship between precedent, res judicata and juridical safety. Although both precedent and res judicata are instrumental to the provision of juridical safety, problems may nevertheless arise from the coexistence of these two institutes in the Brazilian Law. In an innovative way, this dissertation intends to answer, based on the themes examined, the question whether the precedent formed against the res judicata, before or after this being published, will exist, will be null or might be rescinded. The methodological approach adopted here is juridical-dogmatic, dealing with the internal elements of the objective order